The Use Extract of Siam Leaf Eupatorium odoratum L. as Alternative Material In Lowering Blood Glucose - Ulfah Nur Amaliah; Eva Johannes; Munif S Hasan; Elis Tambaru (Hasanuddin University, 2019)
The use of medicine as oral hypoglycemic and insulin have some limitation, the treatment for diabetics needs more expensive cost relatively because it uses in the long term and can give the unwanted side effect. At the recent time, one of the conducted efforts is by using the plant as alternative medicine. This research aims to know the potential of leaves’ extract and to know the effectiveness of siam weed leaves extract’s dosage which most effectivein lowering the level of blood glucose in mice which is induced by alloxan. On this research, anti-diabetic effect of siam weed leaves was observed to male mice which had been induced by alloxan until the level of blood glucose >200 mg/dl. The given treatment orally was conducted during seven days with three variations of dosage concentration of infused extract, they are 5%, 10% and 20 %. Furthermore, it was also used the comparison i.e. infused extract of cinnamon bark with 10 % concentration. Data analyse used SPSS 23.0 program with one way ANOVA then was continued by using Duncan test. The research result shows that the siam weed leaves extract with dosage concentration 5%, 10% and 20% can decrease blood glucose level on mice that have suffered hyperglycemia and most effective on 20%. Thus, it can be concluded that siam weed leaves extract have the potential in lowering blood glucose.